First-principles analysis of ferromagnetic properties of molybdenum-doped wide-band-gap oxides. (2nd September 2019) - Roy, Sujata; Luitel, Homnath; Sanyal, Dirtha
ABSTRACT: The possibility of ferromagnetic ordering in four different Mo-doped oxide semiconductors has been studied theoretically using density functional theory. All four systems, namely Mo-doped TiO2, SnO2, MgO and ZnO, show energetically stable ferromagnetic ordering. In addition, the Mo-doped MgO system shows half-metallic ferromagnetism. From magnetic density calculations, it has been found that for all systems, the 4d electrons of the dopant Mo atoms are the main source of magnetism. Bader analysis shows a higher positive charge on Mo in the case of TiO2 and SnO2 compared to MgO and ZnO.